A Critical Review of The Sociology of Knowledge of Karl Mannheim - Farhang Ershad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper is a critical review of the book, The Sociology of Knowledge of Karl Mannheim, written by M. Ashtiani. The main aim of this attempt is to acquire a more acute understanding of the subject matter of sociology of knowledge and to emphasize the importance of this branch of general sociology in Iran. The specific goal of the paper is trying to have a critical review of Ashtiani’s work to get help to achieve the main aim of this study. The present book includes five chapters: the first two chapters are specified to the scientific biography of Karl Mannheim and his life condition in Hungary, Germany and Britain. In the third chapter, the sphere of sociology of knowledge in view of Mannheim is described; and the two last chapters are about the main concepts and categories of Mannheim’s sociology of knowledge, and finally, the critiques of Ashtiani to the main element of sociology of knowledge of Karl Mannheim.